Fuel Taxes versus Efficiency Standards – An Instrumental Variable Approach - Manuel Frondel; Colin Vance (Rheinisch-Westfälisches Institut für Wirtschaftsforschung (RWI), 2013)
Using household travel diary data collected in Germany between 1997 and 2012, we employ an instrumental variable (IV) approach to estimate fuel price and efficiency elasticities. The aim is to gauge the relative impacts of fuel economy standards and fuel taxes on distance traveled. We fi nd that the magnitudes of the elasticity estimates are statistically indistinguishable: higher fuel prices reduce driving by the same degree as higher fuel efficiency increases driving. This finding indicates an off setting effect of fuel efficiency standards on the effectiveness of fuel taxation, calling into question the efficacy of the European Commission's current efforts to legislate CO2 emissions limits for new cars given prevailing high fuel taxes. – – Auf Basis von Mobilitätsdaten für deutsche Haushalte (1997-2012) und einem Instrumentvariablen-Ansatz schätzen wir Kraftstoffpreis- und Energieeffizienzelastizitäten, um die relativen Effekte von Effizienzstandards und Benzinsteuern auf die Fahrleistung zu erforschen. Es zeigt sich, dass die Größe der beiden Elastizitäten statistisch ununterscheidbar ist: Eine Erhöhung von Benzinsteuern reduziert die Fahrleistung im selben Maße wie eine prozentual gleich starke Effizienzverbesserung diese erhöht. Dieses Ergebnis deutet darauf hin, dass Effizienzstandards die Effektivität von Benzinsteuern mindern, und stellt so die Wirksamkeit der CO2-Emissionslimits für Neuwagen in Frage. Vor diesem Hintergrund sollte die Europäischen Kommission die vorgesehene erhebliche Verschärfung der Emissionsgrenzwerte für Neuwagen bis zum Jahr 2020 noch einmal hinterfragen.
Keywords: D13; Q41; 330; automobile travel; panel estimation models; rebound effect